2006
DOI: 10.1086/505911
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Spectral Catalog of Bright BATSE Gamma‐Ray Bursts

Abstract: We present a systematic spectral analysis of 350 bright GRBs observed with BATSE, with high spectral and temporal resolution. Our sample was selected from the complete set of 2704 BATSE GRBs, and included 17 short GRBs. To obtain well-constrained spectral parameters, four different photon models were fitted and the spectral parameters that best represent each spectrum were statistically determined. A thorough analysis was performed on 350 time-integrated and 8459 time-resolved burst spectra. Using the results,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

87
673
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(768 citation statements)
references
References 38 publications
(1 reference statement)
87
673
4
Order By: Relevance
“…Five percent of the bursts in this sample are short GRBs (with durations less than 2 s). Kaneko et al (2006) find that the most common value for the low-energy slope of the photon spectra is α ∼ −1, and therefore the distribution of the low-energy indices is not consistent with the value predicted by the standard synchrotron emission model in fast cooling regime, -3/2 (Sari et al 1998). The distribution of the peak energies of the time-integrated spectra of long BATSE GRBs has a maximum at ∼250 keV and a very narrow width 100 keV.…”
Section: Grb Samplesmentioning
confidence: 66%
See 1 more Smart Citation
“…Five percent of the bursts in this sample are short GRBs (with durations less than 2 s). Kaneko et al (2006) find that the most common value for the low-energy slope of the photon spectra is α ∼ −1, and therefore the distribution of the low-energy indices is not consistent with the value predicted by the standard synchrotron emission model in fast cooling regime, -3/2 (Sari et al 1998). The distribution of the peak energies of the time-integrated spectra of long BATSE GRBs has a maximum at ∼250 keV and a very narrow width 100 keV.…”
Section: Grb Samplesmentioning
confidence: 66%
“…A systematic spectral analysis of a subsample of 350 bright GRBs selected from the complete set of 2704 BATSE GRBs, in the energy range ∼30 keV−2 MeV observed by BATSE was performed by Kaneko et al (2006;see also Preece et al 2000). Five percent of the bursts in this sample are short GRBs (with durations less than 2 s).…”
Section: Grb Samplesmentioning
confidence: 99%
“…of some GBM-GRBs extends to higher energies compared to BATSE (Kaneko et al 2006). However, this is of no surprise as Amati et al (2002) demonstrated that bursts with higher fluence, i.e.…”
Section: Analysis Of the Gbm Datamentioning
confidence: 99%
“…Most bright GRB spectra can be fit by the Band model (Band et al 1993) which is an empirical function comprising two smoothly broken power-laws, with the distributions of the low energy and high energy power-law photon indices around values of α = −1 and β = −2.2 respectively (Kaneko et al 2006). A thermal component of the prompt emission has also been proposed (e.g.…”
Section: Introductionmentioning
confidence: 99%